2019
DOI: 10.4103/abr.abr_166_18
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effect of Intravenous Ketamine and Electroconvulsive Therapy in Major Depression: A Randomized Controlled Trial

Abstract: Background: Achieving a rapid onset and durable methods of treatment for major depressive disorders is an issue pursuing in psychiatry. This study was designed to assess the therapeutic efficacy of intravenous (IV) ketamine injection in controlling depressive symptoms in comparison with electroconvulsive therapy (ECT) in major depressed disordered patients. Materials and Methods: Thirty-two patients over 18 years of age who were candidates for ECT were enrolled in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 12 publications
1
16
0
Order By: Relevance
“…As shown in Figure 1 , from 856 records screened on title and abstract, 150 full texts were analyzed. The review process led to the selection of 22 studies (references reported in Table 1 ) referring to 22 independent RCTs (Loo et al, 2012 ; Zarate et al, 2012 ; Price et al, 2014 ; Rasmussen et al, 2014 ; Yoosefi et al, 2014 ; Alizadeh et al, 2015 ; Murrough et al, 2015 ; Singh et al, 2016 ; Zhong et al, 2016 ; Anderson et al, 2017 ; Fernie et al, 2017 ; Ray-Griffith et al, 2017 ; Chen et al, 2018 ; Taylor et al, 2018 ; Zhang et al, 2018 ; Dong et al, 2019 ; Fedgchin et al, 2019 ; Kheirabadi et al, 2019 ; Domany et al, 2020 ; Ochs-Ross et al, 2020 ; Keilp et al, 2021 ; Zou et al, 2021 ), 20 of these trials provided quantitative outcome data, therefore were included in the quantitative synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 1 , from 856 records screened on title and abstract, 150 full texts were analyzed. The review process led to the selection of 22 studies (references reported in Table 1 ) referring to 22 independent RCTs (Loo et al, 2012 ; Zarate et al, 2012 ; Price et al, 2014 ; Rasmussen et al, 2014 ; Yoosefi et al, 2014 ; Alizadeh et al, 2015 ; Murrough et al, 2015 ; Singh et al, 2016 ; Zhong et al, 2016 ; Anderson et al, 2017 ; Fernie et al, 2017 ; Ray-Griffith et al, 2017 ; Chen et al, 2018 ; Taylor et al, 2018 ; Zhang et al, 2018 ; Dong et al, 2019 ; Fedgchin et al, 2019 ; Kheirabadi et al, 2019 ; Domany et al, 2020 ; Ochs-Ross et al, 2020 ; Keilp et al, 2021 ; Zou et al, 2021 ), 20 of these trials provided quantitative outcome data, therefore were included in the quantitative synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…There are six papers at present [37]. While randomized control trials [38][39][40] are discussed in three papers, the other three cover open-label trials [41][42][43]. The results suggest that ketamine therapy develops antidepressant effects more quickly than ECT, but perhaps the effect is not sustained compared with ECT.…”
Section: Ketamine As An Alternative To Ectmentioning
confidence: 99%
“…Moreover, our group and others have reported cumulative antidepressant effects with repeated infusions that lead to increased patient response rates over time [10][11][12], with further prolongation with once-weekly maintenance infusions in previously treatment-resistant depression [10]. Overall, ketamine appears to yield higher response rates than other pharmacological treatment strategies for depression; however, only a few randomized controlled trials have directly compared ketamine with other antidepressant interventions [13,14].…”
Section: Introductionmentioning
confidence: 96%